ANALYSIS OF THE ORGANIZATIONAL CONTEXT OF NURSING PRACTICE IN A PUBLIC HOSPITAL IN THE PROVINCE OF CORRIENTES IN ARGENTINA - Patricia Natalia Méndez; Javier Gonzalez-Argote (Revista Científica Arbitrada de la Fundación MenteClara, 2022)
This article analyzes the organizational context for the provision of nursing care in a public hospital in Corrientes. descriptive, observational, cross-sectional study was carried out. The population consisted of 53 nurses. The instrument used was the Nursing Works Index Nursing Practice Environment Scale, which consists of 31 items, grouped into 5 dimensions. Among the characteristics and profile of the participants, there was a massive presence of women (77.4%), 43.4% had a Bachelor's degree in Nursing. In the analysis of the environments, although a higher score was observed in the male gender than in the female gender, when comparing the three that make up the questionnaire, no significant differences were found in any of them. The same behavior was found in the behavior of these factors in relation to the level of education. When analyzing the correlation between the factors of the practice environment with the age of the participants only a statistically significant negative correlation was found with the "Fundamentals of quality of care". Conclusions: An assessment was successfully developed using the PES-NWI tool. Improving awareness of this issue in the workplace is one of the main strategies of the organization in the development of its professionals.